Impact of animation and language on banner click-through rates - Zorn, Steffen; Olaru, D.; Veheim, T.; Zhao, S.; Murphy, J. (California State University, 2012)
This field experiment tested the impact of animation and language on the click-through rate (CTR) of banner advertisements across two website types. Animation results of over one million banner impressions were inconsistent for social networking and information websites. As expected, two languages, English and Norwegian, showed insignificant CTR differences. The CTR was under one tenth of one percent (0.1%), consistent with low reported CTRs for traditional advertising banners. The study contributes to research in testing different website design elements, an under researched area.